Inovasi Pembelajaran Muhadatsah di Pesantren Nurul Huda : Penerapan Metode Practice Rehearsal Pair dengan Dukungan Media Canva - Syifa Nurhaliza; Yuniar; Rendi Sabana (JPG: Jurnal Pendidikan Guru, 2026)
Muhadatsah learning in Islamic boarding schools requires innovation that can improve fluency, confidence, and participation of students in speaking Arabic. The dominant teaching practice of lectures often makes students less active, so a more effective innovative approach is needed. This study aims to examine innovations in muhadatsah learning through the application of the Practice Rehearsal Pair method supported by Canva media at the Nurul Huda Sukawinatan Islamic boarding school. This study uses a mixed methods approach, combining qualitative data from observations, interviews, and documentation, as well as quantitative data from a Likert scale questionnaire to measure the students' responses and improvement in their abilities. The results show that this combination of methods and media significantly improves the students' activity, confidence, and mastery of dialogue based on qualitative and quantitative analysis. Canva helps present attractive visual material, while the Practice Rehearsal Pair method reinforces intensive paired practice. Quantitative analysis using a paired t-test showed a 2-tailed p value < 0.0001, which is less than the significance level of 0.05, so Ho was rejected and H₁ was accepted, indicating an increase in speaking skills after the treatment. In conclusion, this mixed methods-based learning innovation is effective in improving the quality of muhadatsah learning and is feasible to be applied as an instructional strategy.